2021
DOI: 10.7759/cureus.13008
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Sheath Diameter: Correlation With Intra-Ventricular Intracranial Measurements in Predicting Dysfunctional Intracranial Compliance

Abstract: Background Ultrasonographic (USG) measurement of optic nerve sheath diameter (ONSD) has been proposed as a non-invasive, bedside method to detect raised intracranial pressure (ICP) in various clinical settings. We aimed to correlate the ONSD obtained from ultrasonography with the gold standard, intraventricular ICP, and to find out the cut-off point which predicts ICP accurately at different levels. Methodology A prospective double-blind study was carried out by performing ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Invasive methods for ICC measurement pose the risk of bleeding and infection. Hence, many studies have tried to estimate the equivalent of ICC indirectly based on the relationship of ICP and/or ICC with other noninvasive measurable parameters such as the optic nerve sheath diameter ( Sekhon et al, 2014 ; Sahu et al, 2021 ), transcranial Doppler outputs ( Bellner et al, 2004 ; Rockswold, 2004 ), the cranium characteristics ( Russegger and Ennemoser, 1990 ; Ueno et al, 1998 ; Mascarenhas et al, 2012 ), ICP pulse waveform ( Brasil et al, 2021 ), and cerebral blood flow characteristics ( Bateman, 2000 ; Egnor et al, 2001 ; Balédent et al, 2004 ). However, these methods have limitations and errors in ICC measurement ( Raksin et al, 2003 ; Kazimierska et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive methods for ICC measurement pose the risk of bleeding and infection. Hence, many studies have tried to estimate the equivalent of ICC indirectly based on the relationship of ICP and/or ICC with other noninvasive measurable parameters such as the optic nerve sheath diameter ( Sekhon et al, 2014 ; Sahu et al, 2021 ), transcranial Doppler outputs ( Bellner et al, 2004 ; Rockswold, 2004 ), the cranium characteristics ( Russegger and Ennemoser, 1990 ; Ueno et al, 1998 ; Mascarenhas et al, 2012 ), ICP pulse waveform ( Brasil et al, 2021 ), and cerebral blood flow characteristics ( Bateman, 2000 ; Egnor et al, 2001 ; Balédent et al, 2004 ). However, these methods have limitations and errors in ICC measurement ( Raksin et al, 2003 ; Kazimierska et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, intraoperative monitoring of ICP in such high-risk patients is necessary.Therefore, intraoperative monitoring of ICP in such high-risk patients is necessary.But there is no unified standard for evaluating ICP in non-craniocerebral surgery patients during the operation. Studies have shown that ultrasound monitoring of ONSD is a reliable bedside method to assess ICP [13,28], and different studies have different predictive values for intracranial hypertension [29][30]. In the two groups of patients in this study, the average ONSD in the Trendelenburg position and 60 min after pneumoperitoneum were significantly increased (4.5-5.0 mm) but did not reach the critical value of predicting intracranial hypertension (5.5 mm) [29].…”
Section: Discussionmentioning
confidence: 53%
“…Studies have shown that ultrasound monitoring of ONSD is a reliable bedside method to assess ICP [13,28], and different studies have different predictive values for intracranial hypertension [29][30]. In the two groups of patients in this study, the average ONSD in the Trendelenburg position and 60 min after pneumoperitoneum were significantly increased (4.5-5.0 mm) but did not reach the critical value of predicting intracranial hypertension (5.5 mm) [29]. Some studies have shown that when ONSD was at least 6 mm, ICP was greater than 20 mmHg [30].…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Sahu et al, a significant correlation of ONSD with ICP (r = 0.532, p = 0.002) was found. An ONSD threshold of 5.5 mm predicted ICP > 20 mmHg with high sensitivity (100%) and specificity (75%) (area under receiver operating characteristic (ROC) curve = 0.904, p=0.01) in their study [14].…”
Section: Discussionmentioning
confidence: 90%